Effect of memantine on rat and human NMDA receptors in comparison with harmonia axyridis extract - Rehman, Abdul (2023)
Alzheimer's disease results in neuronal cell death, accumulation of amyloid-beta plaques, hyperphosphorylation of tau proteins, and ultimately, impairment of memory. Due to excessive glutamate in the synaptic cleft, NMDA receptor-dependent neurotransmission may be upregulated resulting in an excessive influx of Ca2+ ions causing excitotoxicity. Currently, memantine is the only drug approved by the FDA targeting NMDA receptor-mediated excitotoxicity. NMDA receptors consist of combinations of two GluN1 and GluN2 subunits forming a hetero-tetrameric structure.